2020
DOI: 10.1371/journal.pone.0230446
|View full text |Cite
|
Sign up to set email alerts
|

Physician decision-making and recommendations for stroke and myocardial infarction treatments in older adults with mild cognitive impairment

Abstract: Evidence suggests that older adults with mild cognitive impairment (MCI) might not receive evidence-based treatments. We explored the impact of patient MCI on physician decisionmaking and recommendations for acute ischemic stroke (AIS) and acute myocardial infarction (AMI) in a pilot concurrent mixed-methods study of physicians recruited from one academic center. The mailed survey included a clinical vignette of AIS or AMI where the patient cognitive status was randomized (normal cognition, MCI, or early-stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…36,37 Some providers may assume that patients with cognitive impairment prefer less treatment due to perceived lower life expectancy or worsened quality of life. 35 However, our findings are consistent with previous studies suggesting that those with cognitive impairment do not prefer fewer life-extending treatments. 23 Education efforts may be necessary to improve providers' understanding of cognitive impairment prognosis and treatment preferences associated with cognitive impairment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…36,37 Some providers may assume that patients with cognitive impairment prefer less treatment due to perceived lower life expectancy or worsened quality of life. 35 However, our findings are consistent with previous studies suggesting that those with cognitive impairment do not prefer fewer life-extending treatments. 23 Education efforts may be necessary to improve providers' understanding of cognitive impairment prognosis and treatment preferences associated with cognitive impairment.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have found that patients with preexisting MCI have a lower probability of receiving evidence‐based treatments following acute myocardial infarction or acute ischemic stroke 36,37 . Some providers may assume that patients with cognitive impairment prefer less treatment due to perceived lower life expectancy or worsened quality of life 35 . However, our findings are consistent with previous studies suggesting that those with cognitive impairment do not prefer fewer life‐extending treatments 23 .…”
Section: Discussionsupporting
confidence: 88%
“…The incidence of cerebral hemorrhage in the loading dose group was significantly higher than that in the group without a loading dose. This may reflect the complexity and uncertainty of clinical decision-making ( 28 ) and a higher risk of ischemic and bleeding incidence in the real world ( 29 ). However, a larger sample of data is needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…18 Another possible explanation for patients with MCI receiving elective surgical care less often could be that primary care providers who commonly refer patients for elective surgery may be less likely to refer patients with MCI, believing that they are at higher risk for surgery and may not participate in follow up care as consistently compared with patients with normal cognition. 19…”
Section: Discussionmentioning
confidence: 99%